2009
DOI: 10.1126/scisignal.2000643
|View full text |Cite|
|
Sign up to set email alerts
|

Only a Subset of Met-Activated Pathways Are Required to Sustain Oncogene Addiction

Abstract: Cells addicted to different oncogenic receptor tyrosine kinases develop common downstream mechanisms to sustain malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 56 publications
5
95
0
Order By: Relevance
“…2d). These data are in agreement with the known anti-apoptotic effects of HGF/SF (16,17) and with protection of MET-dependent caspase cleavages by HGF/SF (30,32). These results demonstrated that the GAB1 adaptor is cleaved by caspases under stress induction, leading to the generation of a unique and stable 35-kDa GAB1 fragment containing its central region.…”
Section: The Down-expression Of Gab1 In Stress Conditions Is Associatsupporting
confidence: 90%
“…2d). These data are in agreement with the known anti-apoptotic effects of HGF/SF (16,17) and with protection of MET-dependent caspase cleavages by HGF/SF (30,32). These results demonstrated that the GAB1 adaptor is cleaved by caspases under stress induction, leading to the generation of a unique and stable 35-kDa GAB1 fragment containing its central region.…”
Section: The Down-expression Of Gab1 In Stress Conditions Is Associatsupporting
confidence: 90%
“…Modulation of the EGFR signaling pathway. A, the EGFR pathway interaction map is adapted from Bertotti and colleagues (41) and indicates the phospho-proteins measured by Bio-Plex analysis in pink, and proteins determined by immunohistochemistry on the tissue microarray or by Western blot in yellow. B, the heatmap clusters the samples and phospho-proteins by similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Although MET signaling is primarily mediated by the Ras-MAPK and PI3K-AKT pathways (Bertotti et al 2009), other downstream effectors such as NF-kB, b-catenin, and STAT3 have been linked to MET. NF-kB contributes to HGF/SF-mediated proliferation and tubulogenesis through ERK1/2 and p38 MAPK (Muller et al 2002).…”
Section: Gab1 Gab1 H G F / S F H G F / S F Hgf/sfmentioning
confidence: 99%